European Databases on Stability and Compatibility of Injectable Medicinal Products in Europe - Hecq Jean-Daniel; Krämer Irene; Vigneron Jean (De Gruyter, 2020)
In hospitals, the majority of medication therapy is administered intravenously. Especially, in intensive care units, simultaneous of various injectable drugs is a common practice Drug incompatibilities have been reported to be associated with up to 60 % of all serious and life-threatening adverse drug events. Several databases are used by hospital pharmacists to answer the questions of (in)compatibility of co-administered injectable drugs. The objective of this article is to present the European databases on compatibility and stability of injectable drugs. According to a questionnaire which was sent to the National Hospital Pharmacy Associations of the 28 countries of European Community there are three national databases available in EU countries which are in alphabetical order, Belgium, France and Germany. The Belgian database is dedicated to injectable medications, is updated and distributed annually in French language on a USB key. STABILIS® is an international database giving information with pictograms translated into 29 languages. This database contains also monographs of non-injectable drugs. The internet-based ADKA STABIL-Datenbank is focused on anticancer drug therapy, listing detailed datasets in German language on stability and compatibility including the references.